Understanding water quality management technology and applications - Eckenfelder, W. Wesley 1926-2010 (DEStech Publications, 2004)
Annotation This professional reference presents specialized information about the sources of water pollution and the techniques now in use to improve water quality.
Keywords: Water quality management.; Water -- Purification.; elektronické knihy; electronic books